JAMINAN KREDIT DENGAN PEMBEBANAN HAK TANGGUNGAN ATAS OBJEK TANAH PADA PT. BANK JATIM - Nugroho, Widhi Cahyo (JHP17 (Jurnal Hasil Penelitian), 2022)
Execution of Mortgage is not easy when it is based on the grosse deed and debt acknowledgment, and there is resistance /verzet from the debtor through the District Court which causes the execution of guarantees to take a long time. Therefore,it becomes a matter of legal protection of creditors and debtors in credit guarantee agreements based on UUHT, and aboutthe implementation of APHT in (Bank Jatim) Research method with an empirical juridical approach, which is to approachthe problem by exploring facts referring to the study of applicable regulations (especially Law No.4 of 1996 concerningUnderwriting Rights), the results of the study show that the legal protection of mortgage rights in the UUHT againstcreditors is administrative protection, as creditors who have preferential rights (Article 13 UUHT). for debtors, theexistence of a partial roya as a deviation, a promise that can limit the first mortgage right holder to sell the object of themortgage right on his own power in accordance with Article 6 and Article 11 paragraph (2) letter e,